(untitled) (Stamford Journal of Microbiology, 2017)
Coughing is a physiological process of clarifying the mucosal obstruction through the airways is often be complicated by the invasion following infection by an array of microorganisms. A number of anti-cough formulations are available to combat coughing which is a non-antibiotic drug by nature; however, in some instances these drugs may exhibit anti-microbial trait in action probably due to the chemical properties of the contents. Present study aimed to determine such anti-microbial activity of two commonly used anti-cough mixtures which are locally formulated by the reputed pharmaceuticals in Bangladesh. The antibiotic susceptibility pattern of five laboratory strains of Escherichia coli, Klebsiella sp., Bacillus cereus, Pseudomonas aeruginosa and Staphylococcus aureus were tested by the agar well diffusion method against these two oral liquid samples under investigation used as anti-cough drugs. Sample 1 was found to be highly effective against all of the five test organisms whereas sample 2 was found to be effective against four of the tested organisms. Interestingly, even the lowest amount (50 μl) of both drugs were able to mount inhibitory action against at least two test organisms, the highest amount of both drugs have been found to pose more antimicrobial action than their positive control Gentamycin 10 mg. Stamford Journal of Microbiology, Vol.7(1) 2017: 7-9